Self-Reported Reliance on Nonverbal Behaviour - Uhlemann, Max R.; Lee, Dong Yul (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examined the sensitivity of self-reported reliance on nonverbal cues to actvial changes in nonverbal behaviour. One hundred and twenty-seven high school students viewed two stimulus tapes, one tape containing counsellor responsive and the other tape counselor unresponsive behaviour. The students rated the expertness, trustworthiness, and attractiveness of the target person, and indicated the degree to which they relied on nonverbal cues in making their judgments. The results indicated that participants who reported a higher reliance (in contrast to a lower reliance) on nonverbal cues showed a greater sensitivity to changes in nonverbal behaviour.